2015
DOI: 10.1080/17470919.2015.1117987
|View full text |Cite
|
Sign up to set email alerts
|

Salivary testosterone and cortisol are jointly related to pro-environmental behavior in men

Abstract: Recently, cortisol has been suggested to moderate the positive relationship between testosterone and antisocial behavior. More precisely, high testosterone levels have been found to be related to aggressive or dominant behavior especially when cortisol levels were low. In the present study, we aimed to extend these findings to pro-environmental behavior as an indicator of prosocial behavior. In a first step, 147 male participants provided information on their everyday pro-environmental behavior by completing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…Gavrilova and Lindau found that the collection of salivary specimens in older men is feasible and they provide relevant information on conditions of aging [ 32 ]. The levels of salivary sex steroid hormones in this sample are similar to other samples of males aged 57 to 85 and reflect a typical age-related sex steroid decline, as compared to younger male samples [ 30 , 35 ].…”
Section: Discussionsupporting
confidence: 69%
“…Gavrilova and Lindau found that the collection of salivary specimens in older men is feasible and they provide relevant information on conditions of aging [ 32 ]. The levels of salivary sex steroid hormones in this sample are similar to other samples of males aged 57 to 85 and reflect a typical age-related sex steroid decline, as compared to younger male samples [ 30 , 35 ].…”
Section: Discussionsupporting
confidence: 69%
“…For example, previous studies have proved the relationship between oxytocin and positive social behaviors [ 56 , 57 ]. Meanwhile, man, who typically have higher levels of testosterone, would show less positive behaviors [ 54 , 58 ] and more aggressive behaviors [ 59 , 60 ] than women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the amount of testosterone decreases in young fathers of children under 6 months of age; this makes these fathers more prone to take care of the child. In short, testosterone levels adapts to masculine and paternal needs [30,31].…”
Section: The Three Hormonal 'Climates' Of the Cyclementioning
confidence: 99%